2013
DOI: 10.1109/lpt.2013.2281077
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Optical Characterization of Strain Variable PDMS Biconical Optical Fiber Taper

Abstract: We demonstrate a promising fabrication technology and basic optical characteristics of prepared strain variable polydimethylsiloxane (PDMS) biconical optical fiber taper. For its preparation, silicone elastomer Sylgard 184 was used. Strain dependence of the PDMS fiber taper shows up to 140% elastic elongation. In the process of elongation of the PDMS fiber taper, the measured intermodal interference points to its employment for different sensor applications and opens new areas for developing various types of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Upon elongation, the layer thicknesses decreased, and the photonic bandgap spectrum of the multilayer structure were tuned accordingly. PDMS optical waveguide tapers were fabricated via locally stretching and curing PDMS liquid and tested for strain sensing [78] and for optical airflow sensing. [79] J. Missinne et al .…”
Section: Biomaterial-based Optical Waveguidesmentioning
confidence: 99%
“…Upon elongation, the layer thicknesses decreased, and the photonic bandgap spectrum of the multilayer structure were tuned accordingly. PDMS optical waveguide tapers were fabricated via locally stretching and curing PDMS liquid and tested for strain sensing [78] and for optical airflow sensing. [79] J. Missinne et al .…”
Section: Biomaterial-based Optical Waveguidesmentioning
confidence: 99%
“…As another development of material processing on the production of novel POFs for movement analysis, Guo et al [172] presented the design and fabrication of a highly stretchable optical strain sensor based on dye-doped PDMS optical fibers. PDMS is thermally stable, isotropic, homogeneous, and highly transparent in a wide spectral range [173,174], the flexibility and stretchability of the PDMS fiber make it especially attractive for the sensing of large strains. Dye-doping to the PDMS can be achieved by adding dye molecules to the PDMS precursor prior to curing [175].…”
Section: Polymer Optical Fiber Sensors: Applications In Healthcarementioning
confidence: 99%
“…After a large number of experimental studies, it was found that the integrated system prepared by PDMS has the characteristics of low loss, high temperature stability, and sufficient mechanical stability, and the sensitive characteristic of temperature and humidity also began to be concerned. At the same time, many optical fiber waveguides directly made of PDMS were prepared [ 16 , 17 , 18 ]. Due to the good plasticity of PDMS, optical waveguides can easily be fabricated into a variety of different structures, such as knotted, twisted, and tapered fiber.…”
Section: Sensors Coated With the Pdmsmentioning
confidence: 99%